Optimizing the Use of E-Filing to Improve Tax Payment Compliance - Muhammad Rizky Gunawan; Aal Lukmanul Hakim; Mulyadi (DE'RECHTSSTAAT, 2026)
In the Indonesian tax system, self-assessment grants taxpayers full authority to calculate, pay, and report their tax obligations independently. However, in practice, the level of taxpayer compliance remains a challenge faced by the Directorate General of Taxes. This study aims to analyze and develop an optimization model for e-Filing as an effort to improve taxpayer compliance in paying taxes based on the self-assessment system. The research method used is a juridical empirical approach with a statutory regulatory approach. Data analysis was conducted descriptively and analytically to gain an in-depth understanding of the effectiveness of e-Filing and the obstacles faced in its implementation. The results show that although e-Filing simplifies the tax administration process, several obstacles remain, such as varying levels of digital literacy among taxpayers, limited information technology infrastructure, and the need for increased socialization by the tax authorities. The optimization model proposed in this study includes improving taxpayer education, improving the e-Filing technology system, and strengthening regulations related to administrative sanctions for non-compliance. The conclusion of this study is that e-Filing optimization plays a significant role in improving tax payments based on the self-assessment system, but requires synergy between the government, taxpayers, and adequate infrastructure support.